IDENTIFICATION OF ANTIFUNGAL COMPOUNDS FROM LEAF EXTRACT OF EUCALYPTUS CITRIODORA AGAINST ASCOCHYTA RABIEI (Pakistan Journal of Science, 2022)
Ascochyta rabiei (Pass.) Lab. is a highly destructive pathogen of chickpea. In this study, leaf extract of Eucalyptus citriodora was assessed against this pathogen. Bioassays with methanolic extract (0, 05, 1.0, 1.5, …, 4.0%) extract revealed the remarkable antifungal potential of leaf extract where 69–94% reduction in biomass of A. rabiei was recorded. Chloroform fraction of this extract was separated by partitioning the extract in a separating funnel. Using a solvent system of chloroform: n-hexane (20:80), three compounds were detected on TLC plate which were separated through preparative TLC and purified on HPLC. GC-MS of the purified compounds lead to the identification of 3-cyclohexene- 1-ol, 4-methyl-1-(1-methylethyl)- (1), 1-cyclohexene- 1carboxaldehyde, 4-(1-methylethyl)- (2) and eucalyptol (3) that might caused antifungal activity of the extract.
Keywords: Antifungal activity; Ascochyta rabiei; chickpea blight; Eucalyptus citriodora; leaf extract; natural products